Status Kesuburan Tanah Pada Daerah Pertanaman Hortikultura di Kecamatan Landasan Ulin dan Liang Anggang Kota Banjarbaru - Ekka Rindha Setyanie; Muhammad Mahbub; Mariana Mariana (Agroekotek View, 2019)
Intensive land use in agriculture will lead to decreased soil fertility, there fore is a need to maintain soil fertility and productivity. This study lead is to determine the status of soil fertility in horticultural cultivation area in Landasan Ulin and Liang Anggang district of Banjarbaru city. Use study due by purposive sampling method and soil chemical analysis. The implementation of the research consisted of the preparation stage of the field survey to determine the location of the sampling, and selected 10 point location of soil sampling. The implementation stage included sampling and soil chemical analysis in the laboratory consisting of 5 chemical parameters is Cation Exchange Capacity (CEC) and Basic Saturation (BS) with extraction using 1N NH4OAc pH 7 , P-total and K-total with extraction using 25% HCl, C-organik with modified Walkey-Black method used for determine of soil fertility status. The result showed that soil fertility status at the research sites was classified as low soil fertility status criteria, due to the main limiting factor is low CEC value with average value of 15,27 me/100g and with sandy loam texture class up to sand.